A pilot feasibility study of a peer-led mindfulness program for medical students - Danilewitz, Marlon; Bradwejn, Jacques; Koszycki, Diana (Revue canadienne de l'éducation médicale, 2016)
Background: Mindfulness meditation has gained momentum in medical circles for bolstering wellbeing and other facets of professionalism. This study evaluated the feasibility and benefits of a peer-led mindfulness meditation program (MMP) on medical student wellness and professionalism. Method: Pre-clerkship students were recruited and randomized to the 8-week MMP or wait-list. Feasibility outcomes included ease of recruitment, program attendance and homework compliance. Other outcomes included self-reported psychological distress, empathy, self-compassion, mindfulness, altruism and program satisfaction. Results: The MMP decreased levels of stress and enhanced mindfulness, self-compassion and altruism from baseline to post-study. Changes were not significant for the wait-list condition. Although satisfaction with the MMP was high compliance was suboptimal. Conclusions: A peer-led MMP is feasible and may be a promising approach to enhance medical student wellbeing. Further research is needed to explore strategies to improve program compliance in this student population.